2020
DOI: 10.1136/bjophthalmol-2020-317101
|View full text |Cite
|
Sign up to set email alerts
|

Vascular findings in primarily affected and fellow eyes of middle-aged patients with Coats’ disease using multimodal imaging

Abstract: AimsTo investigate the retinal vascular structure and capillary anomalies of affected and fellow eyes of patients with unilateral Coats’ disease using multimodal imaging.MethodsClinical investigation of both eyes of each patient with diagnosed Coats’ disease using ultra-widefield (UWF) fundus imaging, including UWF fluorescein angiography (UWFFA), spectral domain optical coherence tomography (OCT) and optical coherence tomography angiography (OCT-A).ResultsWe analysed 38 eyes of 19 patients with unilateral Coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
0
11
1
Order By: Relevance
“…Shields et al described retinal capillary dropout adjacent to telangiectasia in the peripheral regions on fundus FFA images, ( 2 ) but the existence of macular capillary dropout was unknown. More recently, Brockmann et al reported an enlarged foveal avascular zone in eyes with stage 1–2 Coats' disease (19 eyes) compared with the contralateral eyes, but the difference was not significant ( 12 ). Schwartz et al reported that the parafoveal VD was decreased in eyes with Coats' disease (13 eyes) compared with unaffected contralateral eyes, ( 13 ) but the sample was relatively small and the clinical significance of the decreased VD was not determined.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Shields et al described retinal capillary dropout adjacent to telangiectasia in the peripheral regions on fundus FFA images, ( 2 ) but the existence of macular capillary dropout was unknown. More recently, Brockmann et al reported an enlarged foveal avascular zone in eyes with stage 1–2 Coats' disease (19 eyes) compared with the contralateral eyes, but the difference was not significant ( 12 ). Schwartz et al reported that the parafoveal VD was decreased in eyes with Coats' disease (13 eyes) compared with unaffected contralateral eyes, ( 13 ) but the sample was relatively small and the clinical significance of the decreased VD was not determined.…”
Section: Discussionmentioning
confidence: 98%
“…To achieve this, we enrolled a relatively large number of patients with eyes displaying macular edema or exudation secondary to Coats' disease and followed them for over 18 months. Considering that widefield imaging revealed abnormal peripheral vessels in the unaffected eyes of patients with Coats' disease in prior studies ( 8 , 12 ), widefield imaging of the unaffected eyes was performed in our study at baseline and during the follow-up period to ensure they did not have abnormal vessels or exudation. This allowed us to use the unaffected eyes as a control group.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 4 Some studies have suggested bilateral involvement in adult-onset disease. 4 , 5 Somatic mutations of implicated genes, such as NDP and ABCA4, have been associated with some cases of pediatric Coats disease. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“… 3 , 10 , 11 Laser photocoagulation, cryotherapy, intravitreal anti-vascular endothelial growth factor (anti-VEGF), drainage of subretinal fluid, and vitrectomy have been used in the treatment of Coats disease. 3 , 5 , 12 If left untreated, Coats disease can lead to secondary glaucoma and total retinal detachment. 1 , 2 , 13 …”
Section: Introductionmentioning
confidence: 99%
“… 3 The disease is believed to be congenital but non-familial with a classic predilection towards unilateral presentation in young males, 3 although the bilaterality of the condition has recently been suggested with the imaging of subtle vascular abnormalities in the fellow eye. 4 Classification is based on morphology, with Shields’ classification 5 being the most commonly utilized.…”
Section: Introductionmentioning
confidence: 99%